SPATIAL ANALYSIS: PENDEKATAN METROPOLITAN STATISTICAL AREA UNTUK PERENCANAAN PEMBANGUNAN MANUSIA DI PROVINSI JAWA TENGAH - Khotimah, Dian Rizqi Khusnul (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
Human development is one of the main focus of development in National Medium-Term Development Plan (RPJMN) 2020-2024. This is stated in the third of seven development agendas,